PRODUCTIVITY TRAITS OF LOCAL MOUNTAIN GOAT AND SOME FACTORS AFFECTING THEM - & et al., Alkass (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The aim of the current investigation was to evaluate some reproductive aspects of local mountain goat raised in farm conditions. A total number of 498 does were mated during two successive years. Results revealed that fertility, conception, kidding, productivity and twinning rates averaged 80.72, 87.15, 84.94, 72.29 and 5.22 %, respectively. Litter size at birth and weaning were 1.05 and 0.9 respectively. Also, all above traits were significantly lower in does aged 2.5 years as compared with older does except those of litter size at birth and weaning. Effect of year of mating was found to be significant only on conception rate. Does mated in August resulted in a significant increase in the studied traits compared with that mated in September and October except those in twinning rate, litter size at birth and weaning. The regressions of litter size at birth and twinning rate on dam’s body weights were significant.